The rhetorical foundations of society - Laclau, Ernesto (Verso, 2014)
"The essays collected in this volume develop the theoretical perspective initiated in Laclau and Mouffe's classic "Hegemony and Socialist Strategy", taking it in three principal directions. First, this book explores the specificity of social antagonisms and answers the question "What is an antagonistic relation?"--an issue which has become increasingly crucial in our globalized world, where the proliferation of conflicts and points of rupture is eroding their links to the social subjects postulated by classical social analysis. This leads Laclau to a second line of questioning: What is the ontological terrain that allows us to understand the nature of social relations in our heterogeneous world?" This is a task he addresses with theoretical instruments drawn from analytical philosophy and from the phenomenological and structuralist traditions. Finally, central to the argument of the book is the basic role attributed to rhetorical tropes--metaphor, metonymy, catachresis--in shaping the "non-foundational" grounds of society"--